Regulators of Financial Invulnerability of Ukraine: International Factors of Influence and Accounting Methodology - Тetyana CALINESCU; Ganna LIKHONOSOVA; Оlena ZELЕNKО (Communications of International Proceedings, 2020)
Currently in Ukraine, the problems of external financial vulnerability, assessment of external stability of the economy, analysis of monetary and financial and debt risks do not attract due attention of specialists and civil servants. Based on this, Ukraine is gradually but surely immersed in a new economic and financial crisis, one of the causes of which is the COVID-19 pandemic. The aim of the article is to identify the level of financial invulnerability of Ukraine in modern conditions and under the presser of world pandemic. Methods / approaches: research methodology based on methods of statistic, correlation and comparative analysis; logical and heuristic; extrapolation; Feedback. Results. Is was identified what the most suitable instrument for analyzing the situation in financial system of Ukraine in the international context is the Macroeconomic Imbalance Procedure. The mane indicators of this procedure show what with a high level of external debt burden, the national economy is characterized by low and unstable growth rates, as well as significant vulnerability to external factors Particularly dangerous is the so-called avalanche effect, when high credit risks of investors push up market interest rates, which, in turn, cause an increase in the debt burden, thus triggering a spiral of crisis events. It is determined that a significant trade deficit, low level of international reserves, the negative balance of the international investment position, excessive foreign debt of Ukraine and the unbearable burden of debt payments signal the possibility of a debt crisis and balance of payments crisis in Ukraine in the near future. Conclusions. Thus, the analysis shows that the process of macro-financial stabilization in Ukraine is quite unstable and can be destroyed at any time under the influence of large-scale external shocks or internal shocks. In particular, it is dangerous to reduce the absolute and relative indicators of international reserves; the size of the external debt burden remains at a critically high level, and the amount of short-term debt continues to increase. What is why when it is necessary to choose a methodology for assessing the vulnerability of the financial system and identifying indicators that may indicate its stability, it is impotent to use not individual, but a system of indicators. containing directly as elements of the financial and macroeconomic sector.
Keywords: Financial Invulnerability; International Factors; Accounting Methodology; Macroeconomic Imbalance; Indicators; Financial Regulators.